2022
DOI: 10.7150/ijbs.72952
|View full text |Cite
|
Sign up to set email alerts
|

High Mobility Group A1 (HMGA1): Structure, Biological Function, and Therapeutic Potential

Abstract: High mobility group A1 (HMGA1) is a nonhistone chromatin structural protein characterized by no transcriptional activity. It mainly plays a regulatory role by modifying the structure of DNA. A large number of studies have confirmed that HMGA1 regulates genes related to tumours in the reproductive system, digestive system, urinary system and haematopoietic system. HMGA1 is rare in adult cells and increases in highly proliferative cells such as embryos. After being stimulated by external factors, it will produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 184 publications
0
12
0
Order By: Relevance
“…Reports showed that in cholangiocarcinoma, HMGA1 can induce tumor cell stemness and EMT, and also participate tumor cell proliferation, differentiation, invasion and migration by promoting TRIP13 transcription [29]. In HCC, overexpressed HMGA1 can accelerate growth and migration of cancer cells by blocking the cell cycle, and can also affect in ltration of immune cells in TME and help tumor cells escape [30]. Yang et al reported that PBK can act as a key kinase, and its overexpression can activate the ETV4-uPAR signaling pathway to promote HCC invasion and metastasis [31].…”
Section: Discussionmentioning
confidence: 99%
“…Reports showed that in cholangiocarcinoma, HMGA1 can induce tumor cell stemness and EMT, and also participate tumor cell proliferation, differentiation, invasion and migration by promoting TRIP13 transcription [29]. In HCC, overexpressed HMGA1 can accelerate growth and migration of cancer cells by blocking the cell cycle, and can also affect in ltration of immune cells in TME and help tumor cells escape [30]. Yang et al reported that PBK can act as a key kinase, and its overexpression can activate the ETV4-uPAR signaling pathway to promote HCC invasion and metastasis [31].…”
Section: Discussionmentioning
confidence: 99%
“…In the nucleus, HMGA1 also structurally cooperates with the specificity protein 1 (Sp1) and the activator protein 2 (AP2) ( 60 ), whose overexpression is also a hallmark of male GCTs ( 21 ). Increased expression of HMGA1 has been associated with uncontrolled cell growth and proliferation, cell invasion, resistance to chemotherapy, maintenance of stem-like properties and metastatic spread in many human cancers, including male GCTs ( 61 ). Notably, HMGA1 is a positive regulator of the IGFs system, with its own DNA binding sites within the IGFBP1 gene promoter ( 49 ), and it is also an inducer of matrix metalloproteinases and other genes involved in tumor invasion ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Forced expression of these miRNAs has been shown to decrease HMGA1 protein levels and reduce motility in TCam-2 cells ( 62 ), supporting the idea that HMGA1 could be relevant for determining the aggressive traits of male GTCs. Suppression of HMGA1 has been proposed as a promising strategy for treating these tumors ( 61 ); however, the currently available HMGA1 inhibitors (i.e., distamycin polyamides) lack of specificity ( 63 ), while the potential interfering RNA molecules under development have not yet reached the clinical application stage ( 64 ). Studies on Met as an anticancer agent in male GCTs may help to overcome the problems of high-costs and long implementation time, two prerogatives of new drugs.…”
Section: Discussionmentioning
confidence: 99%
“…22 HMGA proteins play a role in cancer initiation and development, and they have been proposed as a suitable target to interfere with neoplastic transformation. 13,15,23 Therefore, we decided to search for new small molecules that were able to bind the minor groove of AT-rich DNA sequences that could act as HMGA competitors. To this aim, a docking-based virtual screening was carried out to evaluate the ability of a proprietary in-house natural product library to target the minor groove of AT-rich DNA sequences and to compete with HMGA for the interaction with DNA.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The oncogenic role of these proteins has been demonstrated by their overexpression in vitro in cellular models and in vivo in transgenic mice. Indeed, many of their biological functions actively promote the acquisition of most cancer hallmarks and their multiple oncogenic activities have been extensively reviewed. …”
Section: Introductionmentioning
confidence: 99%